ADVERTISING DAN PROMOSI PENJUALAN PRODUK AGRIBISNIS - Ahya Kamilah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
Advertising is one of the important main promotion tools that can influence the efficacy of selling work progress. Therefore good advertising will make female worker in face to face selling easier. Selling promotion is a kind of communicationform and influenced the progress buying behavior in agribisnis product of the potential consumer so the purpose is to explain consumer about the benefit and value from the agribisnis product.